Differentiation of Methods for Determining the Beginning of the Month of Muharram 1446 H in the Perspective of Islamic Law - Muhammad Abdul Aziz; Ahmad Izzuddin; Muhyar Fanani; Ahmad Adib Rofiudin (Universitas Islam Negeri Mataram, 2024)
The report of the Ministry of Religious Affairs of the Republic of Indonesia on the determination of the beginning of the month of Muharram 1446 H which falls on Sunday raises differences with perukyat and hisab from Nahdhatul Ulama' which makes disputes among Muslim communities. The purpose of this research, to complete a deficiency in existing studies by looking back at how the method of determining the beginning of the month of Muharram 1446 H has been implemented by the Ministry of Religion of the Republic of Indonesia and Nahdhatul Ulama' has been realized or not, has opened a place of difference. This writing uses a normative legal method, which uses an Islamic Law approach. And this research uses primary data which includes in-depth interviews with academics from lecturers, students, and Muslim communities. The results obtained show that there are factors of differentiation in the method of determining the beginning of the month of Muharram 1446 H due to the existence of different provisions. The Ministry of Religious Affairs of the Republic of Indonesia sets the beginning of the month of Muharram 1446 H or on July 07, 2024 because the hilal is above the MABIMS criteria. And Nahdhotul Ulama' set the date of July 8, 2024 based on the Hadith of the Prophet Muhammad SAW. It is Nahdhotul Ulama' to normalize the calculation of the moon to be even 30 days in determining the beginning of the month of Muharram 1446 H.